2015
DOI: 10.1039/c4dt03426k
|View full text |Cite
|
Sign up to set email alerts
|

Uninterrupted galvanic reaction for scalable and rapid synthesis of metallic and bimetallic sponges/dendrites as efficient catalysts for 4-nitrophenol reduction

Abstract: Here, we demonstrate an uninterrupted galvanic replacement reaction (GRR) for the synthesis of metallic (Ag, Cu and Sn) and bimetallic (Cu-M, M=Ag, Au, Pt and Pd) sponges/dendrites by sacrificing the low reduction potential metals (Mg in our case) in acidic medium. The acidic medium prevents the oxide formation on Mg surface and facilitates the uninterrupted reaction. The morphology of dendritic/spongy structures is controlled by the volume of acid used for this reaction. The growth mechanism of the spongy/den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It has been reported that the transition metals such as Au, ,, Ag, , Pt–Ni, Pd–Ag, and Ni–Co can catalyze the reduction of 4-nitrophenol by NaBH 4 . It is widely accepted that the following two steps are involved in the transition-metal-catalyzed reduction of 4-nitrophenol by NaBH 4 : , (1) The BH 4 – ions first chemically adsorb on metal surface and then release highly active hydrogen radicals, which are also adsorbed on metal surface. (2) The adsorbed hydrogen radicals react with adsorbed 4-nitrophenol (or 4-nitrophenolate) to produce 4-aminophenol (or 4-aminophenolate), or they react with water to generate H 2 , which can reduce 4-nitrophenol (or 4-nitrophenolate) in solution.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the transition metals such as Au, ,, Ag, , Pt–Ni, Pd–Ag, and Ni–Co can catalyze the reduction of 4-nitrophenol by NaBH 4 . It is widely accepted that the following two steps are involved in the transition-metal-catalyzed reduction of 4-nitrophenol by NaBH 4 : , (1) The BH 4 – ions first chemically adsorb on metal surface and then release highly active hydrogen radicals, which are also adsorbed on metal surface. (2) The adsorbed hydrogen radicals react with adsorbed 4-nitrophenol (or 4-nitrophenolate) to produce 4-aminophenol (or 4-aminophenolate), or they react with water to generate H 2 , which can reduce 4-nitrophenol (or 4-nitrophenolate) in solution.…”
Section: Resultsmentioning
confidence: 99%
“…81 According to the report by Barman and Nanda, metallic (Ag, Cu and Sn) and bimetallic sponges (Cu–M, M = Ag, Au, Pt and Pd) were prepared by etching of a low reduction potential metal with sulfuric acid (H 2 SO 4 ). 82 The application of H 2 SO 4 led to a high yield synthesis without side product formation and prevented the oxide formation. The acid concentration and etching time can control the degree of etching and structural features; for a fixed time, increasing the concentration of HNO 3 for dealloying the Au–Cu alloy led to an increase in Cu leaching to give a bigger pore size and thicker ligaments.…”
Section: Synthesis Of Nanospongesmentioning
confidence: 98%
“…83 While nitric acid is the most commonly used etchant for chemical dealloying due to strong oxidizing nature, other etchants such as citric acid, ferric nitrate, sulfuric acid, and ammonia have also been reported. 75,[81][82][83] It is important to note that dealloying does not entirely remove the less noble metal and that the residual remaining of less noble metal can signicantly improve the electrocatalytic activity. 80 3.1.2 Electrochemical dealloying.…”
Section: Dealloyingmentioning
confidence: 99%